Artificial conservation measures on groundwater recharge, irrigation potential and productivity of crops of Bharkatia Watershed, Odisha - PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2020)
A study was undertaken in Bharkatia watershed in Athagarh Block of Cuttack District, Odisha during 2011-2014. The objective of the research work was to study the recharge of groundwater through different recharge structures like dug wells, tanks, recharge pit, tube wells, check dams etc., the resulting rise of ground water level and study the impact on increasing irrigation area, production and productivity of different crops in the watershed. Up to the year 2011, no conservation measures were taken up in the watershed. However, in 2011, twenty recharge dug wells, twenty recharge farm ponds, two recharge tube wells, 1120 recharge pits and one check dam were constructed in the watershed. Data on groundwater table rise, irrigation area and productivity of different crops throughout the study period of 4 years were collected and anlysed. The study reveals that average groundwater table came up by 0.27, 0.40 and 0.35 m during pre-monsoon, monsoon and post-monsoon periods in 3 years period after construction of various conservation structures with an average rise of 0.34 m. Increased groundwater recharge helped in augmenting the groundwater potential in the watershed. Because of increased groundwater irrigation, the cropped area in the watershed increased by 308 ha in 3 years period. The productivity of different crops also increased. The yield of kharif and rabi paddy increased by 36.8 and 17.1% in 2014 as compared to 2011 when no conservation measures were taken up for groundwater recharge. The yield of other crops including vegetables also increased substantially due to application of more irrigation water from the raised groundwater table.